PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN REWARDTERHADAP KINERJA PEGAWAI(Studi pada Pegawai PT TASPEN (Persero) Surakarta) - Prasetyanti, Ipung Safitri, Drs. Yuli Tr Cahyono, M.M., Akt., CA (2016)
The purpose of this research to examine and analyze the influence of work environment, motivation, and reward on employees performance at TASPEN(Persero)Surakarta. The amount of the sample in this research is 37 employees. The sampling techniques in this research uses saturated sample method, the entire population is used as a sample. The data analysis in this research uses the help of SPSS version 22. The analysis method that is used is multiple linear regression to test and prove the research hypothesis. The analysis showed that work environment, motivation, and reward have a significant effect on employee performance. This can be seen from the value tcount > ttabel and the probability of < 0,05. Keywords: work environment, motivation, reward, employee performance